Republic of Mozambique : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This Selected Issues paper on Mozambique provides an assessment of direct taxation and options to strengthen tax administration. The study analyzes the question of why Mozambique accumulated unsustainable debt, and discusses the potential factors of the evolution of the debt burden over time. The report also describes the characteristics and causes of rural poverty, the issues to be addressed for its reduction, and analyzes the opportunities and constraints facing smallholder agriculture and cash cropping. It also provides a statistical appendix report for the country.